An analysis of social relationships quality associations with hope among young Italians: The tole of NEET status - Simões, F.; Marta, E.; Marta, E.; Marzana, D.; Alfieri, S.; Pozzi, M. (Journal of Applied Youth Studies, 2021)
Hope is a personal trait stemming from both individual and social factors, including social relationships. Bearing that in mind, we tested how social support quality, described in terms of Basic Psychological Needs Satisfaction (BPNS), is linked with hope dimensions of agency and pathways among young Italians in general and across those Neither in Employment nor in Education or Training (NEET). These associations were examined controlling for several individual factors (e.g., educational level). A total of 3034 participants aged 20 to 35 years (M age = 27.80 years; SD = 4.70) were involved. We found that greater levels of BPNS were linked with stronger pathways and agency levels among the participants in general. Participants’ lower educational and financial satisfaction and those fitting in the NEET category presented significantly worse agency levels. We discuss these results in the context of declining institutional support in the school-to-work transition and young people’s growing reliance on informal support in Italy, as well as its specific meaning for Italian NEETs.